Cogredient Standard Forms of Symmetric Matrices over Galois Rings of Odd Characteristic. (19th July 2012) - Cao, Yonglin
Abstract : Let R = GR ( p s, p s m ) be a Galois ring of characteristic p s and cardinality p s m, where s and m are positive integers and p is an odd prime number. Two kinds of cogredient standard forms of symmetric matrices over R are given, and an explicit formula to count the number of all distinct cogredient classes of symmetric matrices over R is obtained.